Wage Inequality, Firm Size and Gender: The Case of CANADA - Islam, Sadequl; Safavi, Mohammad (Archives of Business Research, 2020)
Using data from the Labor Force Survey, February 2006 and 2019 of Canada, we document a decrease in wage inequality for females and males. In 2006 and 2019, wage inequality in small firms is higher than large firms and much of overall wage inequality occurs within groups (firm size and sex) rather than between groups.